2017
DOI: 10.1186/s12862-016-0845-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying predictors for the spatial diffusion of avian influenza virus in China

Abstract: BackgroundAvian influenza virus (AIV) causes both severe outbreaks and endemic disease among poultry and has caused sporadic human infections in Asia, furthermore the routes of transmission in avian species between geographic regions can be numerous and complex. Using nucleotide sequences from the internal protein coding segments of AIV, we performed a Bayesian phylogeographic study to uncover regional routes of transmission and factors predictive of the rate of viral diffusion within China.ResultsWe found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 54 publications
(64 reference statements)
4
40
0
Order By: Relevance
“…In other words, counties with a larger proportion of surface water received virus more frequently compared to those with less surface water. Surface water resources have been associated with HPAI dispersal and prevalence in China and may signify movement of virus by migrating waterfowl that stopover in lakes, rivers and wetlands [40,51]. In our analysis, this variable was only weakly supported, had a relatively small effect size and was not supported once the model was adjusted for county group sample size.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In other words, counties with a larger proportion of surface water received virus more frequently compared to those with less surface water. Surface water resources have been associated with HPAI dispersal and prevalence in China and may signify movement of virus by migrating waterfowl that stopover in lakes, rivers and wetlands [40,51]. In our analysis, this variable was only weakly supported, had a relatively small effect size and was not supported once the model was adjusted for county group sample size.…”
Section: Discussionmentioning
confidence: 61%
“…The implementation of a GLM into a Bayesian discrete trait analysis has been previously applied to HPAI in China [40] and Egypt [41], providing evidence that environmental, agricultural and anthropogenic factors influence viral movement. Due to differences in social, governmental and agricultural systems, the generalization of these previous GLM results to other countries may not be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Taking H5N1 as an example, a discrete phylogeographic analysis of HPAI H5N1 in Chinese poultry revealed many wellsupported viral lineage movements among provinces (as previously noted in ref. 16). In addition to this general pattern, we further observed that lineage movements occur between pairs of provinces that are adjacent or close ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of fully specified models, with and without distance, and sensitivity analysis (SI Appendix, Fig. S4), we recomputed these phylogeographic analyses using a much smaller set of predictors, specifically those that have been hypothesized by others to affect the large-scale dissemination of AIV (6,8,16,18): 1) the intensity of the poultry trade among locations in China, 2) the migration of wild birds among locations in China, and 3) distances along the road network in China (see Methods for details). Although minimum road distance is strongly inversely associated with the dissemination of AIV lineages across a range of model configurations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation